Islamic ecotheology and environmental fatwas in government policy integration: A literature review of Indonesia's strategy to achieve net zero emissions by 2060 - Yuviandze Bafri Zulliandi (Green Governance: Exploring Politics, Social Justice, and the Environment, 2026)
Background: The issues of climate change and global environmental degradation demand collaboration between the government and society, including religious institutions. In Indonesia, the Indonesian Ulema Council (MUI) has issued several environmental fatwas affirming the moral responsibility of Muslims towards nature. However, most previous research has focused on theological aspects and has not addressed how these fatwas are integrated into public policy, particularly in the strategy towards Net Zero Emissions by 2060. This research gap highlights the need for studies linking religious values to national environmental governance. This study aims to analyze the role of MUI environmental fatwas (No. 04/2014, No. 41/2014, and No. 86/2023) in supporting the government's strategy to achieve Net Zero Emissions, and to explain the model for integrating Islamic ecotheology with national climate policy. Methods: The method used is a qualitative literature review, examining fatwa documents, government regulations (Presidential Regulation No. 98/2021, Indonesia's National Development Planning Agency), and international academic literature on faith-based environmental governance. Findings: The research findings indicate that fatwas function in three ways: (1) providing moral legitimacy to environmental policies; (2) encouraging social participation through networks of Islamic boarding schools, mosques, and Islamic organizations; and (3) strengthening public policies with religious ethical values. However, their effectiveness is still limited by the lack of implementation mechanisms, financial support, and institutional incentives. Conclusion: This research broadens the understanding of Islamic ecotheology as the ethical basis for environmental policies, while also providing practical recommendations for the government to involve religious institutions in transition strategies towards low-carbon and sustainable development. Novelty/Originality of this article: The environmental fatwas issued by the Indonesian Ulema Council (MUI) serve as a moral legitimacy for public policy toward achieving Net Zero Emission 2060, while the novelty of this research lies in integrating Islamic ecotheology with national climate policy within a co-governance framework.